Biological monitoring of o‐toluidine in urine pretreated by an enzymatic deconjugation method. Issue 5 (19th April 2019) - Eitaki, Yoko; Nakano, Makiko; Kawai, Toshio; Omae, Kazuyuki; Takebayashi, Toru
Abstract: Objectives: To establish an enzymatic deconjugation method to separately quantify urinary o ‐toluidine (OT), its six metabolites, another six chemicals present in an OT‐processing plant, and one metabolite of p ‐toluidine, and to propose optimal urinary biological monitoring items of OT exposure. Methods: Thirty‐six urine samples of an OT‐processing plant's workers were obtained and pretreated by an enzymatic deconjugation method employing β‐glucuronidase/arylsulfatase for 3 hours at 37°C and measured by liquid chromatograph‐mass spectrometry (LC‐MS). An alkaline hydrolytic pretreatment and 1‐chlorobutane extraction procedure was also examined as a widely used urinary OT measurement method. Results: The 14 chemicals were separated by LC‐MS condition set by us and 13 chemicals other than 2‐chloroaniline showed satisfiable linearity and limits of determination. Standard substances of six OT metabolites decomposed after the alkaline heating. In the 36 urine samples, OT, N ‐(4‐hydroxy‐2‐methylphenyl) acetamide (NHM), and 4‐amino‐ m ‐cresol (ACR) accounted for approx. 90% of the total OT and OT metabolites, but inter‐individual variation of the three substance excretion seemed to be wide. Time course of urinary excretion revealed that concentration of the three substances was higher 24 hours after the work shift's end rather than just after the work shift. Conclusions: OT and its six metabolites can each be determined with LC‐MS. The alkaline method is not so optimal for exact biological monitoring. Rather, the sum of urinary OT, NHM, and ACR measured by the enzymatic method is a better index, and "end of the workweek" is a good urine‐sampling time for the biological monitoring of OT exposure.